Systemic AL Amyloidosis: Current Approaches to Diagnosis and Management - Fotiou, Despina (Hemasphere, 2020)
AL amyloidosis is characterized by a low-level expansion of an indolent, small plasma cell clone that produces amyloidogenic light chains. Amyloid aggregates or preceding intermediaries cause direct cell damage through their proteotoxicity, and amyloid deposits distort tissue architecture, and, eventually, lead to organ impairment. It is a rare, underdiagnosed disease with a diverse clinical presentation depending on the organ tropism of the amyloid fibrils; cardiac and renal involvement is most common, but any organ can be affected, excluding the central nervous system. A high level of awareness and a systematic approach using newly emerging screening biomarkers is required to achieve early diagnosis. Management should be multidisciplinary as supportive management tailored to management of organ dysfunction is paramount to survival and minimization of treatment-associated toxicity. The initial therapeutic aim is to rapidly eliminate the clonal plasma cell that produces the circulating amyloid precursor and achieve a complete hematologic response, and if possible with undetectable minimal residual disease as assessed by next-generation methods (flow and sequencing), with minimal toxicity. Treatment is tailored to the initial risk assessment of the patients. Treatments are based on regimens adapted from the expanding options that are available for multiple myeloma patients and hematological response rates have improved. Organ response rates are strongly associated with deeper hematologic response but usually lag behind hematological response and are also dependent on the initial organ function reserve. Agents directed against the amyloid deposits have been explored to aid amyloid clearance and improve organ function, but data are still negative.